Cross down - Patterson, James, 1947-; DuBois, Brendan (Patterson, James, 1947- Alex Cross series, 2023)
"For the first time, John Sampson is on his own. The brilliant crime-solving duo of Washington, DC's, Metro PD and the FBI has a proven MO: Detective Alex Cross makes his own rules. Detective John Sampson enforces them. When military-style attacks erupt, brutally sidelining Cross, Sampson is sent reeling. The patterns are too random--Sampson's friend, his partner, his brother--have told him. Don't trust anyone. As a shadow force advances on the nation's capital, Sampson alone must protect the Cross family, his own young daughter, and every American, including the president"--